2021
DOI: 10.3892/ol.2021.12535
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of SUMO2/3 antagonizes isoflurane‑induced cancer‑promoting effect in hepatocellular carcinoma Hep3B cells

Abstract: Surgery for patients with complicated liver cancer often results in a long exposure to anesthesia with an increase in side effects. Continued long-term exposure to isoflurane may promote liver cancer progression. Small ubiquitin-like modifier (SUMO) 2 and 3, also known as SUMO2/3, conjugates to substrate proteins when cells undergo acute stress. However, whether or not SUMO2/3 is involved in isoflurane-mediated liver cancer progression is unknown. In the present study, hepatocellular carcinoma (HCC) cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(43 reference statements)
1
2
0
Order By: Relevance
“…Additionally, literature cites SUMO2/3 as a pivotal agent driving colorectal cancer progression and oxaliplatin resistance by orchestrating the sumoylation modification of the DNA assembly constituent, Ku80 [56] . Recent revelations align with our experimental evidence, advocating that SUMO2 exerts a positive regulatory influence on hepatocellular carcinoma progression [ 57 , 58 ]. Concurrently, sumoylation modifications have been firmly established as regulators of CSC stemness [ 15 , 17 ].…”
Section: Discussionsupporting
confidence: 67%
“…Additionally, literature cites SUMO2/3 as a pivotal agent driving colorectal cancer progression and oxaliplatin resistance by orchestrating the sumoylation modification of the DNA assembly constituent, Ku80 [56] . Recent revelations align with our experimental evidence, advocating that SUMO2 exerts a positive regulatory influence on hepatocellular carcinoma progression [ 57 , 58 ]. Concurrently, sumoylation modifications have been firmly established as regulators of CSC stemness [ 15 , 17 ].…”
Section: Discussionsupporting
confidence: 67%
“…In Hep-3B cell line, short-term isoflurane exposure (<12h) might facilitate cancer cell invasion by enhancing the formation of small ubiquitin-like modifier 2 and 3 (SUMO2/3) conjugates, a kind of stress indicators, while the inhibitor of SUMO2/3 could reverse the response (29). But in primary cultured cells from patients undergoing hepatectomy and general anesthesia, evidence indicated that isoflurane could reduce HCC aggressiveness via down-regulating PI3K/AKT signaling pathway mediated nuclear factor kappaB (NF-kB) activity (30).…”
Section: Isofluranementioning
confidence: 99%
“…SENP3 , in combination with ARID1A and CSMD has also been proposed as an effective prognosis marker in HCC, despite molecular heterogeneity detected in HCC patients [ 118 ]. In HCC, it has also been shown that SENP3 overexpression significantly reduces isoflurane-mediated stimulation of sumoylation, resulting in decreased proliferation and invasion of HCC cells [ 117 ].…”
Section: Sumo Proteases In Cancermentioning
confidence: 99%